2013
DOI: 10.1186/1472-6963-13-235
|View full text |Cite
|
Sign up to set email alerts
|

Developing a complex intervention for the outpatient management of incidentally diagnosed pulmonary embolism in cancer patients

Abstract: BackgroundMost patients with pulmonary embolism (PE) spend 5–7 days in hospital even though only 4.5% will develop serious complications during this time. In particular, the group of patients with incidentally diagnosed PE (i-PE) includes many patients with low risk features potentially ideal for outpatient management; however the evidence for their optimal management is lacking hence relative practices may vary considerably. We describe the development process, components, links and function of a nurse-led se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
22
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 23 publications
0
22
0
Order By: Relevance
“…Results were used to refine the programme in order to produce the finalised programmeLovell et al 2008 [35]UKGuided self-help intervention for depression in primary careMRC framework 2000Synthesise available evidence on the effectiveness of the intervention, identify key factors that may moderate effectiveness and deal with uncertainties emerging from the reviews, assess of acceptability to patients and healthcare professionalsMeta-regression, meta-analysis and a consensus process with experts, including academics ( n  = 8), health professionals ( n  = 10) and service users ( n  = 1), phone interviews with patients and healthcare professionalsThe integration of findings allowed identifying the ‘core components’ of the intervention, which was then tested in feasibility study. The intervention did not moved to the RCT phase, as it did not markedly improve outcomes in the exploratory studyMunir et al 2013 [42]UKWork-related guidance tool for people with/recovering from cancerIntervention mapping [36]Obtain consensus on the questions included in the guidance tool (a list of 43 questions was previously developed) and to which healthcare professional these should be asked, and test feasibility of the intervention to participantsA two-round Delphi study conducted online with 172 experts (round 1) and 139 experts (round 2); online survey to participants ( n  = 38) who tested the guideline tool for six weeksThe intervention was finalised by identifying the key components of the tool and a range of stakeholders and the tested in a feasibility studyMurchie et al 2007 [37]UKFollow-up programme for people treated for cutaneous malignant melanomaMRC framework 2000Seek patients and GPs’ views on feasibility, desirability, benefits and components of the programme; assess feasibility and identify problems or deficienciesSteering group consultations, semi-structured interviews with patients ( n  = 9) and GPs ( n  = 14), pre-pilot operationalisation exerciseThe components of the intervention were identified, fine-tuned and the final intervention tested in a feasibility studyPalmer et al 2013 [29]UKNurse-led intervention for the outpatient management of incidentally diagnosed pulmonary embolism in cancer patientsMRC framework 2008Real-time re-modelling, refinement and optimisation of the intervention to respond to problems and deviations arising in practiceObservations, audit and surveyThe intervention processes and delivery were refined on the basis of the real-time re-modelling process’ resultsRedfern et al 2008 [36]UKThe Stop Stroke intervention to improve risk factor management after strokeMRC framework 2000Achieve consensus about the factors which a novel intervention should address and how this might be delivered and test feasibility of intervention components to patients and healthcare professionalsConsensus process involving a study steering group (a team of multidisciplinary experts) and local clinicians, researchers and stroke survivors, semi-structure interviews with patients and h...…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Results were used to refine the programme in order to produce the finalised programmeLovell et al 2008 [35]UKGuided self-help intervention for depression in primary careMRC framework 2000Synthesise available evidence on the effectiveness of the intervention, identify key factors that may moderate effectiveness and deal with uncertainties emerging from the reviews, assess of acceptability to patients and healthcare professionalsMeta-regression, meta-analysis and a consensus process with experts, including academics ( n  = 8), health professionals ( n  = 10) and service users ( n  = 1), phone interviews with patients and healthcare professionalsThe integration of findings allowed identifying the ‘core components’ of the intervention, which was then tested in feasibility study. The intervention did not moved to the RCT phase, as it did not markedly improve outcomes in the exploratory studyMunir et al 2013 [42]UKWork-related guidance tool for people with/recovering from cancerIntervention mapping [36]Obtain consensus on the questions included in the guidance tool (a list of 43 questions was previously developed) and to which healthcare professional these should be asked, and test feasibility of the intervention to participantsA two-round Delphi study conducted online with 172 experts (round 1) and 139 experts (round 2); online survey to participants ( n  = 38) who tested the guideline tool for six weeksThe intervention was finalised by identifying the key components of the tool and a range of stakeholders and the tested in a feasibility studyMurchie et al 2007 [37]UKFollow-up programme for people treated for cutaneous malignant melanomaMRC framework 2000Seek patients and GPs’ views on feasibility, desirability, benefits and components of the programme; assess feasibility and identify problems or deficienciesSteering group consultations, semi-structured interviews with patients ( n  = 9) and GPs ( n  = 14), pre-pilot operationalisation exerciseThe components of the intervention were identified, fine-tuned and the final intervention tested in a feasibility studyPalmer et al 2013 [29]UKNurse-led intervention for the outpatient management of incidentally diagnosed pulmonary embolism in cancer patientsMRC framework 2008Real-time re-modelling, refinement and optimisation of the intervention to respond to problems and deviations arising in practiceObservations, audit and surveyThe intervention processes and delivery were refined on the basis of the real-time re-modelling process’ resultsRedfern et al 2008 [36]UKThe Stop Stroke intervention to improve risk factor management after strokeMRC framework 2000Achieve consensus about the factors which a novel intervention should address and how this might be delivered and test feasibility of intervention components to patients and healthcare professionalsConsensus process involving a study steering group (a team of multidisciplinary experts) and local clinicians, researchers and stroke survivors, semi-structure interviews with patients and h...…”
Section: Resultsmentioning
confidence: 99%
“…Interventions were delivered in a variety of settings (e.g. inpatient, outpatient clinics and home-based settings) and targeted a wide range of conditions, such as mental health conditions [28, 30, 35, 40, 47], stroke [31, 36, 39], cancer [29, 32, 33, 37, 42] and other chronic illnesses [25, 34, 38]. Two studies reported on preventive interventions targeting older people [24, 50] and one on a programme to empower patients undergoing gynaecological surgery during the perioperative period [43].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations